The silence that precedes the word - Oliveira, José Regino de (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
What’s the difference between comical and non-comical performance? What moment defines that a comic performance will be a success? With these concerns, it was proposed to the actors of the Celeiro de Antas Theater Group a research project that consisted of investigating the instant, the moment that precedes the scenic action, which we started to call “The Silence That Precedes the Word.” The starting point was to investigate whether there is a specific conduct that, once adopted, favors the emergence of laughter at the moment an action. And the group spent five months speculating and discussing these subtleties. This article aims to record the paths and results of this investigation.